2004
DOI: 10.1074/jbc.m311989200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Physiologically Relevant Substrates for Cloned Gal: 3-O-Sulfotransferases (Gal3STs)

Abstract: Sulfated glycoconjugates regulate biological processes such as cell adhesion and cancer metastasis. We examined the acceptor specificities and kinetic properties of three cloned Gal:3-O-sulfotransferases (Gal3STs) ST-2, ST-3, and ST-4 along with a purified Gal3ST from colon carcinoma LS180 cells. Gal3ST-2 was the dominant Gal3ST in LS180. While the mucin core-2 structure Gal␤1,4GlcNAc␤1,6(3-O-MeGal␤1,3)GalNAc␣-O-Bn (where Bn is benzyl) and the disaccharide Gal␤1,4GlcNAc served as high affinity acceptors for Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…Only in one case here, when both termini of a core 2 O-glycan (m/z 1747) were sialylated, could the diagnostic ions at m/z 195/234 for an internal 6-sulfo GlcNAc (GlcNAc6S) be detected for the precursor derived from the non-GlcNAc6ST-transfected parent SW480 cells. The predominance of Gal3S is consistent with previous reports indicating the dominant presence of Gal3ST2 in normal and cancer colonic cells (30,44). Due to this lack of other sulfation possibilities, the monosulfated O-glycan structures that could be deduced for SW480 have the lowest isomeric variation, with the major ones shown by the cartoon drawings on their respective MS 2 spectra (Fig.…”
Section: Identification Of Monosulfated O-glycan Structuressupporting
confidence: 90%
“…Only in one case here, when both termini of a core 2 O-glycan (m/z 1747) were sialylated, could the diagnostic ions at m/z 195/234 for an internal 6-sulfo GlcNAc (GlcNAc6S) be detected for the precursor derived from the non-GlcNAc6ST-transfected parent SW480 cells. The predominance of Gal3S is consistent with previous reports indicating the dominant presence of Gal3ST2 in normal and cancer colonic cells (30,44). Due to this lack of other sulfation possibilities, the monosulfated O-glycan structures that could be deduced for SW480 have the lowest isomeric variation, with the major ones shown by the cartoon drawings on their respective MS 2 spectra (Fig.…”
Section: Identification Of Monosulfated O-glycan Structuressupporting
confidence: 90%
“…A sulfated Lewis x determinant was identified as a major structural motif in mucins produced by human colon carcinoma cells 1b. Previous studies from our group 20a,b indicated that two distinct Gal 3- O -sulfotransferases (Gal3STs) in tumor tissues and cancer cells exhibited distinct acceptor preferences. Enzymes from colon cancer cell lines and colon tumor tissues prefer to sulfate the C-3 position of Gal in the Galβ1,4GlcNAcβ moiety of the mucin core 2 structure.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, enzymes from breast cancer cells prefer to act on the Galβ1,3GalNAcα moiety. Therefore, to determine the structural features of the mucin core 2 that influence Gal3ST activity, assay was undertaken with compounds 4 and 5 for various sulfotransferases 20c. As compared to their activities toward the acceptor Galβ1,4GlcNAcβ1,6(3-OMeGalβ1,3)GalNAcα-O-Bn, LS180 Gal3ST, Gal3ST-2, and Gal3ST-3 exhibited poor activity (12−16%) toward compound 4 and as anticipated, negligible activity (1−2%) toward compound 5 ; Gal3ST4 showed only 23% activity with compound 5 as compared to its activity toward 3-OMeGalβ1,4GlcNAcβ1,6(Galβ1,3)GalNAcα-OBn.…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about the functional role of GAL3ST2, a member of the galactose-3-O-sulfotransferase protein family, in human types of cancers. However, a recent series of evidence indicates that downregulation of GAL3ST2 expression is observed in colon cancers, and GAL3ST2 has also been implicated in the metastatic potential of breast and laryngeal cancers (23)(24)(25). Considering the mounting evidence on the central role of selectins such as galectin-3 in thyroid, pancreatic, colon and even GCs in relation to several relevant genes, the associative function of Gal:3-O-sulfotransferase in GCs should be emphasized and evaluated in more detail (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%